Auditory Perceptual Learning in Adults with and without Age-Related Hearing Loss - Karawani, Hanin; Bitan, Tali; Attias, Joseph; Banai, Karen (Frontiers in Psychology, 2016)
Introduction : Speech recognition in adverse listening conditions becomes more difficult as we age, particularly for individuals with age-related hearing loss (ARHL). Whether these difficulties can be eased with training remains debated, because it is not clear whether the outcomes are sufficiently general to be of use outside of the training context. The aim of the current study was to compare training-induced learning and generalization between normal-hearing older adults and those with ARHL. Methods : Fifty-six listeners (60–72 y/o), 35 participants with ARHL, and 21 normal hearing adults participated in the study. The study design was a cross over design with three groups (immediate-training, delayed-training, and no-training group). Trained participants received 13 sessions of home-based auditory training over the course of 4 weeks. Three adverse listening conditions were targeted: (1) Speech-in-noise, (2) time compressed speech, and (3) competing speakers, and the outcomes of training were compared between normal and ARHL groups. Pre- and post-test sessions were completed by all participants. Outcome measures included tests on all of the trained conditions as well as on a series of untrained conditions designed to assess the transfer of learning to other speech and non-speech conditions. Results : Significant improvements on all trained conditions were observed in both ARHL and normal-hearing groups over the course of training. Normal hearing participants learned more than participants with ARHL in the speech-in-noise condition, but showed similar patterns of learning in the other conditions. Greater pre- to post-test changes were observed in trained than in untrained listeners on all trained conditions. In addition, the ability of trained listeners from the ARHL group to discriminate minimally different pseudowords in noise also improved with training. Conclusions : ARHL did not preclude auditory perceptual learning but there was little generalization to untrained conditions. We suggest that most training-related changes occurred at higher level task-specific cognitive processes in both groups. However, these were enhanced by high quality perceptual representations in the normal-hearing group. In contrast, some training-related changes have also occurred at the level of phonemic representations in the ARHL group, consistent with an interaction between bottom-up and top-down processes.